Pneumonectomy after response to gefitinib treatment for lung adenocarcinoma. (August 2013) - Funakoshi, Yasunobu; Takeuchi, Yukiyasu; Maeda, Hajime
A 69-year-old Japanese woman who had never smoked had lung adenocarcinoma harboring epidermal growth factor receptor mutation. After 8 months of gefitinib treatment, salvage pneumonectomy was performed. Microscopic examination showed that non-responsive adenocarcinoma remained although necrosis was prominent. Postoperatively, the patient developed empyema that was successfully managed. The postoperative empyema after treatment with gefitinib should be noted, as well as the finding that residual viable tumor cells remained even after the dramatic radiographic response.